Sustainable occupational safety and health at the workplace - Azuddin Bahari; Hanum Hassan; Ishak Jainoo (Penerbit Universiti Malaysia Perlis, 2013)
This book will also assist the readers and those involved in the business sector to understand the relevant laws, identify hazards, assess risk and control risk in the workplace and implement the Occupational Safety and Health Management System.